Separation and identification of microplastics in marine organisms by TGA-FTIR-GC/MS: A case study of mussels from coastal China. (1st March 2021) - Liu, Yi; Li, Ruojia; Yu, Jianping; Ni, Fengli; Sheng, Yingfei; Scircle, Austin; Cizdziel, James V.; Zhou, Ying
Abstract: Microplastics are ubiquitous in the marine environment but characterizing them in marine organisms is challenging. Herein we describe a method to detect, identify, and quantify microplastics in marine mussels ( Mytilus edulis ) using thermal gravimetric analysis – Fourier Transform infrared spectroscopy – gas chromatography mass spectrometry (TGA-FTIR-GC/MS) after extracting and isolating the microplastics using chemical digestion, density separation, and filtration. Combining the three instrumental techniques adds discriminatory power as temperature profiles, chromatograms, and vibrational and mass spectra differ among common plastics. First, we tested several digestion schemes after spiking the mussels with plastics commonly found in the marine environment, including polyethylene (PE), polystyrene (PS), polypropylene (PP) and polyvinyl chloride (PVC). KOH (10%, w/v) was the most suitable reagent, providing good recoveries (>97%) without degrading the microplastics. We show that the technique TGA-FTIR-GC/MS can be optimized to readily determine both the type (polymer) and amount (mass) of microplastics in the sample. Applied to 100 mussels from each of six locations along the coast of China, we found an average of 0.58 mg of plastic per kg of tissue (range 0.16–1.71 mg/kg), with PE being the most abundant type of plastic measured. Among the coastal cities, mussels from Dalian had the highest microplastic content. Overall, we demonstrate that the method is a powerful technique to quantify masses of microplastics in marine mussels, a species commonly used as a bioindicator of pollution, and may be applied to other biota as well. Graphical abstract: Image 1 Highlights: Effective method to identify and quantify microplastics in mussels. KOH (10%, w/v) frees microplastics from the tissues without damaging them. Recoveries for mussels spiked with microplastics were >97%. Method applied to mussels from 6 cities along the coast of China. Each sample had microplastics with PE the most abundant type.